2011
DOI: 10.1590/s0103-84782011001200002
|View full text |Cite
|
Sign up to set email alerts
|

Rates of nitrogen and growth retardant trinexapac-ethyl on wheat

Abstract: The objective in this study was to evaluate the effects of nitrogen rates in association with rates of the growth retardant trinexapac-ethyl on wheat. The experiment was conducted in Viçosa, MG and arranged in a 5×4 factorial, randomized block design, with four repetitions. A combination of five nitrogen rates (30, 60, 90, 120 and 150kg ha -1 ) with four rates of trinexapac-ethyl (0, 62.5, 125 and 187.5g ha -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
0
12
0
5
Order By: Relevance
“…Entretanto, na cultura do arroz, também Alvarez et al (2007) e Nascimento et al (2009) observaram que a aplicação de ETX afetou a produtividade da cultura. Corroborando essas informações, Espíndula et al (2011) relataram reduções da produtividade do trigo com o uso do ETX. Por outro lado, Buzetti et al (2006) observaram que o uso do regulador de crescimento (cloreto de clormequat) não afetou a produtividade do arroz.…”
Section: Variável Equaçõesunclassified
See 1 more Smart Citation
“…Entretanto, na cultura do arroz, também Alvarez et al (2007) e Nascimento et al (2009) observaram que a aplicação de ETX afetou a produtividade da cultura. Corroborando essas informações, Espíndula et al (2011) relataram reduções da produtividade do trigo com o uso do ETX. Por outro lado, Buzetti et al (2006) observaram que o uso do regulador de crescimento (cloreto de clormequat) não afetou a produtividade do arroz.…”
Section: Variável Equaçõesunclassified
“…No Brasil, esses produtos são utilizados como maturadores de cana-de-açúcar e promovem aumento de rendimento de açúcar, sem impacto negativo na qualidade do caldo, no conteúdo de fibras ou na massa de colmos (Viana et al, 2008). Têm sido utilizados com sucesso na cultura do trigo, visando à redução da altura de plantas, evitando o acamamento (Zagonel & Fernandes, 2007;Espíndula et al, 2011). Para a cultura do arroz de terras altas, ainda existem poucas informações sobre a aplicação de biorreguladores, visando a reduzir a altura das plantas e seus efeitos nos componentes de produção e produtividade da cultura (Buzetti et al, 2006;Alvarez et al, 2007;Nascimento et al, 2009).…”
Section: Introductionunclassified
“…According to MATYSIAK (2006) the cereal grain yield may also be increased in case of a lack of permanent crop lodging. Some authors observed that retardants have influence on the number of seeds per ear and the mass of thousand grains but the influence is often the retardant type or rate depended (ESPINDULA et al, 2009;ESPINDULA et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Espindula et al (2009) found quadratic responses of grain yield for rates that varied from 30 to 150 kg ha -1 . Espindula et al (2011) reported higher grain yield of wheat 'Pioneiro' (adapted to Brazilian Savanna) with 100 kg N ha -1 in the same soil and similar climatic conditions. Corroborating these results, Espindula et al (2010) reported maximum grain yield with 96.8 kg N ha -1 with the same cultivar.…”
Section: Introductionmentioning
confidence: 85%
“…Corroborating these results, Espindula et al (2010) reported maximum grain yield with 96.8 kg N ha -1 with the same cultivar. These authors found yields of 4800 and 5000 kg ha -1 (Espindula et al, 2011). In Brazilian Savanna conditions, Trindade et al (2006) report a maximum grain yield of 5 733 kg ha -1 (maximum technical efficiency) with 73 kg N ha -1 (economic rate).…”
Section: Introductionmentioning
confidence: 97%